indonesia Pelatihan dan Pendampingan Manajemen karakter pada usia dini Melalui Dukungan orang tua untuk menciptakan sumber daya yang insani di Desa Selat baru: Pelatihan dan Pendampingan Manajemen karakter pada usia dini Melalui Dukungan orang tua untuk menciptakan sumber daya yang insani di Desa Selat baru - Anggi Gusty Fuadhie; Aqillah Alliyah Putri; Muhammad Fauzan Fitratsani; Muhammad Adriansyah; Mahalizikri, Irawan Fahrudin; Susilawati (Jurnal Pengabdian, 2025)
Character management mentoring is a process of improving quality and results that lead to the formation of character and noble morals in a complete, integrated and balanced manner, an activity to sow and foster awareness from parental support of the values contained in Islam.From the long history of the basic education structure that starts from home, namely the support of parents and their environment where this will affect the condition of future generations, it can be concluded that the so-called Character Management is human. Who always want to feel comfortable, without any shortcomings, let alone disturbances that will befall them which ultimately forms their character. Such concerns will certainly never exist. This activity will also reveal the nature of human resources in Islam and from a conventional perspective. As a religion that is blessed by Allah. Ar-Rohmaan ar-Rohiim, it is certain that all aspects related to it such as matters with humans tend to be positive. Islam is a spirit that is manifested from the purity and tranquility of the Islamic religion itself. So,, if the purpose of life in Islam is to worship Allah ar-Rohmaan ar-Rohiim, then character management at an early age actually refers to that purpose. If the sharia outlined by Islam as a provision for the afterlife, it is certain that the values embedded in Islam in the intended order. Thus it can be understood together that Islamic Spirituality is a building of awareness of Muslims in forming character management at an early age, including the process of character management at an early age and support from parents according to Islam. The need for character management at an early age is a dimension of life that can determine the meaning, purpose, suffering and death of a person who will be formed for future purposes.